The effect of game-based learning model with STEM approach in reducing learning anxiety and enhancing science learning motivation among students - Anggraini, Irma Novita; Arif, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2024)
Students' anxiety in science learning can affect their overall abilities. Thus, schools must create a supportive environment to reduce anxiety and foster learning motivation. This study examines the influence of game-based learning models with STEM approaches to decrease learning anxiety and enhance students' learning motivation. The study was conducted at the junior high school level, specifically at SMPN 1 Mlarak Ponorogo. The method employed was quantitative descriptive with questionnaire surveys for 34 students. The research findings, analyzed through MANOVA tests, revealed that the game-based learning model with STEM approaches did not significantly affect students' learning anxiety and motivation. Still, it did influence students' learning outcomes. Consequently, this study suggests that employing game-based learning models enhances students' learning outcomes more effectively than conventional teaching methods. The implications of this study underscore the importance of considering non-academic factors in adopting innovative learning models to support effective teaching and learning practices.